Artistic features of Lydia Kossutskaya’s prose for children (based on the material of the Kazakh literary online magazine Daktil) - Sabirova, D.A.; Nurbaeva, A.M.; Zh.Sh, Sametova; A.U., Baibolov; M.B., Moldagali (Journal of Ecohumanism, 2024)
Children’s literature is a unique means of reflecting ideas existing in society. It plays a vital role in shaping the cultural background of the nation and each individual member of society. The children’s prose of Lydia Kossuthskaya has been little studied, since the writer devotes the main place to prose in her work. The need to expand ideas about the structure of Lydia Kossutskaya’s children’s stories determines the significance of this work. Possessing artistic value, Kossuthskaya’s children’s prose needs thorough research. The novelty of the work lies in the attempt to comprehend the internal patterns of Kossuthskaya’s children’s prose, which can be explored through a consistent and systematic analysis of poetics. The purpose of this article is to analyze L. Kossutskaya’s prose for children from the point of view of the features of her poetics (artistic language). Based on the results obtained, it is possible to expand the understanding of the poetics of children’s stories of both Kossuth and Kazakh literature in general.